PENGARUH EDUKASI GIZI MELALUI VIDEO DAN BOOKLET TERHADAP PPENINGKATAN PENGETAHUAN, SIKAP DAN PERILAKU IBU HAMIL DALAM PENCEGAHAN STUNTING - Amalia, Zuliana; Pamungkasari, Eti Poncorini; Priyatama, Aditya Nanda (Poltekkes Kemenkes Bandung, 2024)
A child is considered stunted if it has delayed growth and development during the first thousand days of life (1000 HPK). This period begins with pregnancy and continues throughout the first two years of life. This condition causes chronic malnutrition. Some main causes of stunting is the lack of mother’s knowledge, attitudes, and behaviors regarding child health and nutrition. Providing educational media, such as video and booklet, containing clear and comprehensive information about nutrition for pregnant mothers can be implemented to improve the limitations in maternal knowledge and understanding. This study aimed to examine the influence of nutritional education media, through videos and booklets, on the knowledge, attitudes, and behaviors of pregnant women in preventing stunting. This study used Research and Development (R&D) method with ADDIE approach. The total population was 1,992 pregnant women in Subulussalam city. Subjects were 44 pregnant women according to the inclusion and exclusion criteria with non-nonprobability sampling technique with purposive sampling type.. The knowledge, attitudes, and behavior data of the pregnant mothers were gathered by conducting pre-test and post-test using questionnaire. The results showed there was a significant effect of the video and booklet on the pregnant mothers’s knowledge in preventing stunting, with a p-value=0.009. There was also a significant effect on the attitudes with p-value=0.006. While the behaviors have p-value=0.017 and showed significant effect as well. It could be concluded that the educational video and booklet of nutrition for pregnant mothers are feasible and can be used as educational media for preventing stunting.